Gastrointestinal Bleeding Secondary to High-Dose Melphalan Pretreatment in Patients with Multiple Myeloma Was Associated with the Mode of Melphalan Administration. (11th July 2022) - Ge, Qunfang; Wang, Yi; Zhu, Huiling; Xu, Kaihong; Sheng, Lixia; Yan, Xiaoyan; Ouyang, Guifang
Abstract : Objective . To analyze the characteristics of gastrointestinal bleeding secondary to high-dose melphalan pretreatment in patients with multiple myeloma. Methods . Between 1 January 2016 and 31 October 2021, 26 patients with multiple myeloma after autologous peripheral blood hematopoietic stem cell transplantation with high-dose melphalan pretreatment were recruited. They were assigned to either the oral administration group or the intravenous administration group according to the administration modes, or to either the gastrointestinal bleeding group or the nongastrointestinal bleeding group. Analyses were performed based on the differences in general gastrointestinal symptoms and hemorrhage between different administration modes and on the differences in the general gastrointestinal symptoms, platelet alterations, and the intestinal microecology before pretreatment between patients with and without gastrointestinal bleeding. Results . Of the 26 included patients, heavy secondary gastrointestinal bleeding was found in 6 patients with intravenous pretreatment. In patients given intravenous melphalan, those with gastrointestinal bleeding showed more pronounced general symptoms such as nausea and vomiting versus those without. There was no significant difference in platelet alterations between the two groups. Gastrointestinal bleeding was associated with more significant microecological disturbances than no bleeding. Conclusion . Gastrointestinal bleeding secondary to high-dose melphalan pretreatment in patients with multiple myeloma was associated with the mode of melphalan administration, adverse symptoms at pretreatment, and the intestinal microecology prior to pretreatment. Thus, improvement of the intestinal microecology prior to pretreatment and mitigation of adverse gastrointestinal symptoms during pretreatment may contribute to a lower incidence of secondary gastrointestinal bleeding and enhanced transplantation safety.